THE EFFECT OF MACROECONOMIC FACTORS ON THE NUMBER OF CORPORATE SUKUK OFFERS IN INDONESIA - Ependi, Haerul; Hakiman Thamrin (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to analyze the effect of macroeconomics factors on corporate sukuk in Indonesia in the short and long term. The independent variable is Inflation, Economics Growth, Total Money Supply, Foreign Exchange Rate and Bank Indonesia (BI) Rate. Whereas the dependent variable is the number of sukuk corporations offered. The results of this study indicate that the Inflation, Economics Growth, Total money supply, and BI Rate have no significant effect on the number of corporate sukuk offered. While Foreign Exchange Rate has significant effect on the amount of corporate sukuk that offered. In the short term period, the total money supply has significant influence on the number of sukuk corporations offered while the rest have no significant effect